PENGARUH MOTIVASI DAN PELAT1HAN KERJA TERHADAP ICINERJA KARYAWAN CV. OBECH PESONA NUSANTARA PACET MOJOKERTO - asjari, fachrudy; dwiarta, i made bagus (Majalah Ekonomi, 2011)
Human Resources is a natural resource that is used to drive and synergizing other resources to achieve organizational goals. The role of an indispensable leader in providing motivation to employees as human resources within the company, so employees have a maximal performance. In addition, training is a factor to be considered also by the company that would become the capital of employees do the job technically and according to procedures within the company. Data collection was done by, observation, interviews, questionnaires and documentation, research conducted on 32 samples of employee respondents rafting CV. OBECH Pesona Nusantara, Pacet, Mojokerto. Using a Likert scale, respondents' answers processed by multiple regression analysis, t test, F test and the test of determination. Ã‚â€¢ The results showed that the sub variable motivation (X1) and training (X2) simultaneously significant or significant effect on employee performance rafting CV. OBECH Pesona Nusantara. This shows that the motivation and training need to be maintained in order to improve employee performance rafting.